2015
DOI: 10.5430/ijhe.v4n1p187
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Commitment to Community Engagement: A Case Study of Makerere University

Abstract: Although the earliest medieval universities began as teaching-only institutions, the university as an institution has since experienced revolutions in the way its functions are conceived. Currently, the university embraces three functions: teaching, research and community engagement. Although the teaching and research functions of the university are much more established than its third function, the importance of community engagement is acknowledged in the academic literature and, to varying degrees, by govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…(2012) observe that, through CE, HEIs can play fundamental roles in empowering stakeholders and communities to outline pathways toward upward mobility. For this reason, governments and politicians since the mid-20 th century encouraged HEIs to halt detaching themselves from outside entities, instead serve as critical instruments in tackling the challenges typically facing societies and local communities ( Franklin, 2009 ; Goddard et al., 2016 ; Mugabi, 2015 ; Pinheiro and Langa, 2015 ). Research has shown that CE is a tremendous bridge between academic institutions, stakeholders, and the general community ( Olowu, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2012) observe that, through CE, HEIs can play fundamental roles in empowering stakeholders and communities to outline pathways toward upward mobility. For this reason, governments and politicians since the mid-20 th century encouraged HEIs to halt detaching themselves from outside entities, instead serve as critical instruments in tackling the challenges typically facing societies and local communities ( Franklin, 2009 ; Goddard et al., 2016 ; Mugabi, 2015 ; Pinheiro and Langa, 2015 ). Research has shown that CE is a tremendous bridge between academic institutions, stakeholders, and the general community ( Olowu, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Community engagement as a scholarly activity helps to prepare the academic staff for their teaching roles through advancement of knowledge and skills in their field to guide the students. This is because the community engagement process also involves consultancy, continuing education and collaborative research in which the academic staff may also participate, not only the students (Mugabi 2015 :193). In addition, there is an opportunity for enquiry-based learning in community engagement, whereby the academic staff and students may conduct fieldwork for further exploration of aspects of their field of study (Miller 2013 :47).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…As such, African nations are embracing the discourse of the knowledge economy and seeking to revitalize their HE systems (Molla & Cuthbert, 2016), with university functions presumed to be progressing from teaching to research, and eventually to community service. Empirical studies on this topic are yet to gain momentum but some studies (Cloete & Maaseen, 2015;Mugabi, 2015;Ofoyuru, 2018;Ogunsanya, Olajumoke, & Govender, 2019, Schalkwyk, 2015 seem to reveal somewhat marginal and fragile situation of university-society engagements in Africa budding in all the three core functions of the university: teaching, research and direct service. Moreover, much of the emphasis still seems to be on teaching and learning (Cloete & Maassen, 2015;Mugabi, 2014;Ogunsanya, Olajumoke, & Govender, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, much of the emphasis still seems to be on teaching and learning (Cloete & Maassen, 2015;Mugabi, 2014;Ogunsanya, Olajumoke, & Govender, 2019). However, these engagement studies are either case studies (Mugabi, 2015;Ofoyuru 2018) or comparative studies of eight universities from Southern and Eastern Africa only (Cloete & Maaseen, 2015;Schalkwyk, 2015). This limits our understanding of the modalities and extents of university-society engagements across African regions.…”
Section: Introductionmentioning
confidence: 99%